1995
DOI: 10.1126/science.270.5234.290
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA Recognition and Bending by Insertions in the α2 Tail of the Yeast a1/α2 Homeodomain Heterodimer

Abstract: The yeast MAT alpha 2 and MATa1 homeodomain proteins bind cooperatively as a heterodimer to sites upstream of haploid-specific genes, repressing their transcription. In the crystal structure of alpha 2 and a1 bound to DNA, each homeodomain makes independent base-specific contacts with the DNA and the two proteins contact each other through an extended tail region of alpha 2 that tethers the two homeodomains to one another. Because this extended region may be flexible, the ability of the heterodimer to discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 27 publications
(9 reference statements)
2
19
0
Order By: Relevance
“…The a1 and ␣2 homeodomain proteins, which bind cooperatively as a heterodimer to hsg sites, interact via a carboxy-terminal tail in ␣2 that tethers the a1 and ␣2 homeodomains together (11,29,30). Amino acid insertions in the extended region of the ␣2 tail suppress defective a1-␣2 sites with increased spacing between the a1 and ␣2 half sites (21). The spatial constraints between ␣2 and Mcm1 are also in contrast with the distance requirements of the human ETS domain proteins, Elk-1 and SAP-1, which bind cooperatively with the MADS box protein, serum response factor (SRF) (47).…”
Section: Discussionmentioning
confidence: 99%
“…The a1 and ␣2 homeodomain proteins, which bind cooperatively as a heterodimer to hsg sites, interact via a carboxy-terminal tail in ␣2 that tethers the a1 and ␣2 homeodomains together (11,29,30). Amino acid insertions in the extended region of the ␣2 tail suppress defective a1-␣2 sites with increased spacing between the a1 and ␣2 half sites (21). The spatial constraints between ␣2 and Mcm1 are also in contrast with the distance requirements of the human ETS domain proteins, Elk-1 and SAP-1, which bind cooperatively with the MADS box protein, serum response factor (SRF) (47).…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that, as expected, circularization of the duplex template so as to compress the major groove by 17-20°over 7 bp results in an increase in TBP binding affinity. The (36) investigated the binding of the al/a2 homeodomain protein heterodimer, which is known to bend duplex DNA so as to compress the minor groove near the center of its bound complex (37). Protein mutants were also studied which possessed one, two or three glycine residues inserted into the linker region which connects the two monomer subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that in the presence of Mcm1 sites were selected from the random pool which have both 5-and 6-bp spacing further shows that binding by the ␣2-Mcm1 complex can accommodate either spacing. In contrast, the spacing requirements between the ␣2 and a1 binding sites of haploid-specific operators, as well as the positions of the binding sites in other homeodomain complexes such as the Drosophila Paired homodimer and the Hox-Pbx heterodimer are rigidly fixed (43,53,54). These results suggest that either the proteinprotein or protein-DNA interactions in the ␣2-Mcm1-DNA complex can adjust, to some extent, to accommodate the alterations in spacing between the binding sites.…”
Section: Discussionmentioning
confidence: 41%
“…Electrophoretic Mobility Shift Assays (EMSAs)-The relative ␣2-Mcm1 DNA binding affinities for the AMSC and mutant operators were determined by EMSA as described previously (43). Labeled DNA fragments containing ␣2-Mcm1 sites were incubated with purified ␣2-(92-210) and Mcm1-(1-96) proteins at the concentrations given in the figure legends at room temperature for 3 h. The ␣2 and Mcm1 proteins used in these experiments were purified as described previously and were greater than 90% pure as judged on Coomassie-stained SDS-polyacrylamide gels (40).…”
Section: Methodsmentioning
confidence: 99%